Questionnaire versus direct technical measurements in assessing postures and movements of the head, upper back, arms and hands - Hansson, Gert-Åke; Balogh, Istvan; Byström, Jeannette; Ohlsson, Kerstina; Nordander, Catarina; Asterland, Paul; Sjölander, Simon; Rylander, Lars; Winkel, Jörgen; Skerfving, Staffan; Malmö Shoulder-Neck Study GroupM3 - doi: 10.5271/sjweh.584 (Scandinavian Journal of Work, Environment & Health, 2001)
' ' OBJECTIVES ': 'This study compares questionnaire-assessed exposure data on work postures and movements with direct technical measurements. ' ' METHODS ': 'Inclinometers and goniometers were used to make full workday measurements of 41 office workers and 41 cleaners, stratified for such factors as musculoskeletal complaints. The subjects answered a questionnaire on work postures of the head, back, and upper arms and repeated movements of the arms and hands (3-point scales). The questionnaire had been developed on the basis of a previously validated one. For assessing worktasks and their durations, the subjects kept a 2-week worktask diary. Job exposure was individually calculated by time-weighting the task exposure measurements according to the diary. ' ' RESULTS ': 'The agreement between the self-assessed and measured postures and movements was low (kappa = 0.06 for the mean within the occupational groups and kappa = 0.27 for the whole group). Cleaners had a higher measured workload than office workers giving the same questionnaire response. Moreover, the subjects with neck-shoulder complaints rated their exposure to movements as higher than those without complaints but with the same measured mechanical exposure. In addition, these subjects also showed a general tendency to rate their postural exposure as higher. The women rated their exposure higher than the men did. ' ' CONCLUSIONS ': 'The questionnaire-assessed exposure data had low validity. For the various response categories the measured exposure depended on occupation. Furthermore, there was a differential misclassification due to musculoskeletal complaints and gender. Thus it seems difficult to construct valid questionnaires on mechanical exposure for establishing generic exposure-response relations in epidemiologic studies, especially cross-sectional ones. Direct technical measurements may be preferable.
Keywords: arm; assessment; goniometer; hand; head; inclinometer; job; mechanical exposure; misclassification; movement; MSD; musculoskeletal disorder; occupation; posture; questionnaire; technical measurements; upper back; workload